PENGEMBANGAN MODUL PRINSIP PENGELOLAAN DAN KESELAMATAN KERJA DI LABORATORIUM BAGI CALON GURU - Risnia Erma Yuliana; Evi Suryawati; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to produce a principle module for management and work safety in the laboratory for prospective teachers. This research was conducted at the Biology Education Study Program Department of Mathematics and Natural Sciences Faculty of Riau University and the Subject Teachers' Association (MGMP) Pekanbaru City, in July - March 2020. The type of research used is Research and Development (R&D) which refers to the ADDIE model with the stages of Analyze, Design, Development, Implementation, and Evaluation. The instrument used in this study was a validation sheet and response questionnaire. Validation is done to assess the validity of the modules that have been developed, namely by validating by the validator and a limited trial phase I by Biology Education Students of FKIP UR semester 8, and limited trial phase II by prospective biology education teachers who have not participated in the PPG. The assessment of the modules developed includes 5 aspects of assessment, namely aspects of module format, graphics, picture illustrations, language, and content eligibility. Module quality based on validity gets a score of 3.26 with a very valid category, and module usage from the limited trial results stages I and II get a score of 3.46 with a very good category. Based on these data it can be concluded that the principles of work management and safety modules in the laboratory for prospective teachers have been categorized as modules that have the potential to be used on a large scale.Key Words: Content Knowledge, Module, Prospective Teachers